Histopathologic spectrum of morphea: a single-center retrospective study (Dermatology Reports, 2024)
Morphea is a rare autoimmune disease that often affects skin and subcutaneous tissues. The aim of this study was to determine the association between patient demographic parameters, lesion site, clinical subtype of morphea, and histological findings. Between 2016 and 2022, we investigated 78 patients with morphea at the Department of Pathology, Prof. Dr. Cemil Taşcıoğlu City Hospital in Turkey. Case-specific hematoxylin and eosin stain slides were obtained from the pathology archive and assessed blindly by two pathologists. Flattening of rete ridges, location of inflammatory infiltrate, grade of inflammatory infiltrate, presence of plasma cells, presence of eosinophils, homogenization of dermal collagen, decrease of skin appendages, basal pigmentation and melanin incontinence were evaluated. Statistical analyses were performed using SPSS Statistics v.20 (IBM, Armonk, NY, USA). The most common clinical presentation was plaque type (87.5%), while histopathological findings included homogenization of dermal collagen (100%) and decrease of skin appendages (98.7%). Flattening of the rete ridges was observed in 46.2% of patients. Severity of the inflammatory infiltrate was found to be higher in these patients (p=0.028). Basal pigmentation was observed in 59% of patients. Line sign was more common in lower extremity lesions among all localizations (p=0.015). The histopathologic features of morphea are variable and confusing. Particularly, in cases with collagen homogenization, morphea should be considered in differential diagnosis with clinical correlation. In addition, the line sign could be helpful for identifying lesions located in the lower extremities.